2005
DOI: 10.1038/sj.bjc.6602720
|View full text |Cite
|
Sign up to set email alerts
|

Fluvastatin synergistically enhances the antiproliferative effect of gemcitabine in human pancreatic cancer MIAPaCa-2 cells

Abstract: The new combination between the nucleoside analogue gemcitabine and the cholesterol-lowering drug fluvastatin was investigated in vitro and in vivo on the human pancreatic tumour cell line MIAPaCa-2. The present study demonstrates that fluvastatin inhibits proliferation, induces apoptosis in pancreatic cancer cells harbouring a p21ras mutation at codon 12 and synergistically potentiates the cytotoxic effect of gemcitabine. The pharmacologic activities of fluvastatin are prevented by administration of mevalonic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
65
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(74 citation statements)
references
References 44 publications
(43 reference statements)
9
65
0
Order By: Relevance
“…Treatment in accordance with the characteristics of the pancreatic cancer cells is needed. Many studies have reported the effectiveness of combination treatment of anticancer drug and inhibitor or gene transduction (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32). There is no treatment that is effective for all carcinomas with various characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment in accordance with the characteristics of the pancreatic cancer cells is needed. Many studies have reported the effectiveness of combination treatment of anticancer drug and inhibitor or gene transduction (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32). There is no treatment that is effective for all carcinomas with various characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…To quantify cyclin D1 mRNA, RNA (1 µg) was reverse transcribed as previously described [25] and the resulting cDNA was diluted (2:3) and then amplified by QRT-PCR with the Applied Biosystems 7900HT sequence detection system. Cyclin D1, validated primer was purchased from Applied Biosystems (Assay ID Hs00277039_m1).…”
Section: Quantification Of Cyclin D1 Gene and Protein Expression In Ementioning
confidence: 99%
“…for 10 min and washed with PBS; the resulting pellet was immediately frozen in liquid nitrogen and stored at À801C. Briefly, RNA (1 mg) was reverse transcribed (Bocci et al, 2005a) and the resulting cDNA was diluted (2 : 3) and then amplified by QRT-PCR with the Applied Biosystems 7900HT sequence detection system. Vascular endothelial growth factorand TSP-1-validated primers were purchased from Applied Biosystems (Assay ID Hs00170236_m1 and Hs00173626_m1, respectively).…”
Section: Assessment Of Human Vegf and Tsp-1 Gene Expression And Plasmmentioning
confidence: 99%